Mapping and clustering the adoption of carbon pricing policies: what polities price carbon and why?. (21st October 2019) - Skovgaard, Jakob; Ferrari, Sofía Sacks; Knaggård, Åsa
ABSTRACT: Carbon pricing, including carbon taxes and emissions trading, has been adopted by different kinds of polities worldwide. Yet, beyond the increasing adoption over time, little is known about what polities – countries as well as sub- and supranational entities – adopt carbon pricing and why. This paper explores patterns of adoption (both implemented policies and those scheduled to be) through cluster analysis, with the purpose of investigating factors that could explain polities' decisions to adopt carbon pricing. The study contributes empirically by studying carbon taxes and emissions trading together and by ordering the polities adopting carbon pricing into clusters. It also contributes theoretically, by exploring constellations of variables that drive the adoption of carbon pricing within individual clusters. We investigated 66 adopted policies of carbon pricing, which were divided into five clusters: early adopters, North-American subnational entities, Chinese pilot provinces, second-wave developed polities, and second-wave developing polities. The analysis indicates that the reasons for adopting carbon pricing have shifted over time. While international factors (climate commitments or influences from polities within the same region) are increasingly salient, domestic factors (including crises and income levels) were more important for the early adopters. Key policy insights Carbon pricing has become a global mainstream policy instrument. Economic and fiscal crises provide windows of opportunity for promoting carbon pricing. The international climate regime can support the adoption of carbon pricing through mitigation commitments and international financial and technical assistance. Learning between polities from the same region is a useful tool for promoting carbon pricing. Carbon intensive economies tend to prefer emissions trading over carbon taxes.